Duration of American Football Play and Chronic Traumatic Encephalopathy - Mez, Jesse (Ann Neurol, 2019)
OBJECTIVE: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with exposure to contact and collision sports, including American football. We hypothesized a dose–response relationship between duration of football played and CTE risk and severity. METHODS: In a convenience sample of 266 deceased American football players from the Veterans Affairs–Boston University–Concussion Legacy Foundation and Framingham Heart Study Brain Banks, we estimated the association of years of football played with CTE pathological status and severity. We evaluated the ability of years played to classify CTE status using receiver operating characteristic curve analysis. Simulation analyses quantified conditions that might lead to selection bias. RESULTS: In total, 223 of 266 participants met neuropathological diagnostic criteria for CTE. More years of football played were associated with having CTE (odds ratio [OR] = 1.30 per year played, 95% confidence interval [CI] = 1.19–1.41; p = 3.8 × 10(−9)) and with CTE severity (severe vs mild; OR = 1.14 per year played, 95% CI = 1.07–1.22; p = 3.1 × 10(−4)). Participants with CTE were 1/10th as likely to have played <4.5 years (negative likelihood ratio [LR] = 0.102, 95% CI = 0.100–0.105) and were 10 times as likely to have played >14.5 years (positive LR = 10.2, 95% CI = 9.8–10.7) compared with participants without CTE. Sensitivity and specificity were maximized at 11 years played. Simulation demonstrated that years played remained adversely associated with CTE status when years played and CTE status were both related to brain bank selection across widely ranging scenarios. INTERPRETATION: The odds of CTE double every 2.6 years of football played. After accounting for brain bank selection, the magnitude of the relationship between years played and CTE status remained consistent. ANN NEUROL 2020;87:116–131